Rations containing corn, sorghum grain, or wheat compared for weaned pigs - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
The feed, required per pound of gain was similar for pigs fed corn, sorghum grain, corn-wheat, or sorghum grain-wheat diets. Pigs on the corn ration grew significantly (P<.05) faster. The sorghum grain, sorghum grain-wheat, and corn-wheat rations each produced similar gains.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Corn; Sorghum grain; Wheat